2011
DOI: 10.1097/rlu.0b013e31820ade17
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of F-18 FDG PET and 201Tl Scintigraphy for Detection of Primary Malignant Bone and Soft-Tissue Tumors

Abstract: FDG PET was found to be more sensitive than Tl scintigraphy for primary malignant bone and soft-tissue tumors, although it was less specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Although a previous meta-analysis 31 has reported that the difference in the SUV mean between malignant and benign soft-tissue tumours was statistically significant, our data showed no significant difference in the SUV mean between them. Yamamoto et al 32 examined the 18 F-FDG PET findings of 40 soft-tissue tumours (33 malignant and 7 benign tumours), and the SUV was higher in malignant lesions than in benign lesions, but this difference was not statistically significant like our study (benign vs malignant: SUV max , 3.71 6 1.20 vs 7.85 6 6.92, p 5 0.26). Shin et al 33 reported that the sensitivity, specificity and diagnostic accuracy of 18 F-FDG PET/CT for diagnosing malignant MS tumours were 80%, 65.2% and 73% with a cut-off SUV max of 3.8, and they mentioned that their results were not as good as other reported results using average cut-off SUV max values from 2.0 to 2.5.…”
Section: Discussionmentioning
confidence: 38%
“…Although a previous meta-analysis 31 has reported that the difference in the SUV mean between malignant and benign soft-tissue tumours was statistically significant, our data showed no significant difference in the SUV mean between them. Yamamoto et al 32 examined the 18 F-FDG PET findings of 40 soft-tissue tumours (33 malignant and 7 benign tumours), and the SUV was higher in malignant lesions than in benign lesions, but this difference was not statistically significant like our study (benign vs malignant: SUV max , 3.71 6 1.20 vs 7.85 6 6.92, p 5 0.26). Shin et al 33 reported that the sensitivity, specificity and diagnostic accuracy of 18 F-FDG PET/CT for diagnosing malignant MS tumours were 80%, 65.2% and 73% with a cut-off SUV max of 3.8, and they mentioned that their results were not as good as other reported results using average cut-off SUV max values from 2.0 to 2.5.…”
Section: Discussionmentioning
confidence: 38%
“…Subsequently, the remaining ones were downloaded and reviewed as full-text versions. Eventually, 42 articles published between 1991 and 2015 were included in our investigation, among which 19 18 36 evaluated bone sarcomas using 18 F-FDG PET, whereas 24 36 59 used PET/CT. The article searching process and exclusion criteria are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 42 articles, 35 19 24 , 27 – 29 , 32 – 34 , 36 52 , 54 59 provided enough data to recalculate sensitivity and specificity and were included in the quantitative analysis, whereas the remaining 7 18 , 25 , 26 , 30 , 31 , 35 , 53 were analyzed qualitatively. One article was published in Chinese 45 and the remainders were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Functional nuclear scans reflect the metabolic activity of tumors and may provide important information regarding the biologic behavior. 201Tl scintigraphy has been used in clinical oncology to estimate the presence and biologic activity of tumors including bone and soft tissue tumors, and the utility of 201Tl scintigraphy has been reported to differentiate malignant tumors from benign lesions in bone and soft tissue [2][3][4][5][6][7][8][9][10][11][12][13]. However, these previous studies were composed of a relatively small number of bone tumors and most of the studies used only visual analysis [2,3,5].…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing interest in using 201Tl scintigraphy for management of bone and soft tissue tumors since the early 1990s [3]. Several studies have reported 201Tl scintigraphy to be an effective diagnostic tool to differentiate malignant from benign areas of interest [2][3][4][5][6][7][8][9][10]. However, there are little published data for 201Tl scintigraphy dealing with only bone lesions [3] and no report has statistically evaluated the diagnostic capacity of 201Tl scintigraphy in a large number of bone lesions.…”
Section: Introductionmentioning
confidence: 98%